Love’s crossing through self-emptying language: Augustine of Hippo’s confessio and Adélia Prado’s mystical poetry - Ribeiro Lin, Davi C. (TEOLITERARIA - Revista de Literaturas e Teologias, 2020)
“Crossing” can be described as a displacement between two points, characterized by a starting point, a path and a point of arrival. In addition to the geographical, exterior voyage, crossing is a metaphor for the wandering heart in via, an inner journey. This work approaches two “boatmen” who propose the crossing of inner life, the 4th-5th century North-African theologian Augustine of Hippo and Brazilian poet Adélia Prado. Augustine and Adélia Prado use self-emptying language, confessio and mystic poetry respectively, to express their existential poverty. While Augustine crushes his pride through the vulnerability of confession, Adélia Prado uses poetic language as spiritual exercise to annihilate her ego. This self-emptying language is not only informative, but performative speech; it is the language that affirms finitude and vulnerability, opening the self to a journey of longing towards an alterity. The ultimate goal of humbling oneself in poetic vulnerability before the Mystery is to capture the dynamic invitation to love. Augustine’s confessional language and Adélia Prado’s poetry foster the passage from self-centeredness to a loving relational center. Adélia Prado can help us read Augustine not only as the doctor of Grace, but as “Doctor Humilitatis”, a reception clouded by centuries of theological discussion.